(untitled) - Sehgal, R. I. (Darya Ganj, New Delhi, 2004)
Contents of material: A global warehouse of information. Three ways to connect to the internet. Usenet newsgroups. How to read newsgroups. Electronic libraries and publicaton. Internet libraries. Three things to know about chatting on the net. Internet terminology.
Keywords: Library information networks,Information retrieval and storage,Integrated library systems ( Computer systems ),Libraris; Automation